Characterization, expression and evolution analysis of NLRC3 , NLRC5 and NLRX1 in Mastacembelus armatus under Aeromonas veronii infection - Shengyue Lin; Kaifeng Wang; Weijian Chen; Ziyan Deng; Guojun Cai; Min Zhang; Zihang Xie; Weibin Li; Chong Han; Qiang Li (Journal of Fish Biology, 2026)
NOD‐like receptors (NLRs) serve as crucial innate immune sensors in multicellular organisms, recognizing diverse pathogen‐associated components and regulating immune responses such as nuclear factor kappa B (NF‐κB) signalling and inflammatory pathways. To elucidate the roles of NLRC3 , NLRC5 and NLRX1 in the innate immunity of the Mastacembelus armatus , this study first characterized these genes and examined their response to Aeromonas veronii infection. We identified the three NLR genes from the M. armatus transcriptome and analysed their evolutionary relationships through domain architecture and maximum likelihood (ML) phylogenetic reconstruction. All three NLR proteins contained conserved NACHT and leucine‐rich repeat (LRR) domains, and ML phylogenetic analysis grouped M. armatus with other Synbranchiformes and Perciformes, consistent with established taxonomy. Tissue expression profiling in healthy fish revealed constitutive expression of all three genes across nine examined tissues, with significantly higher levels in gills, suggesting their involvement in frontline mucosal immunity. Temporal expression analysis in spleen, liver and kidney following A. veronii challenge showed distinct organ‐specific patterns: although all three genes were downregulated in the liver, they were significantly upregulated in spleen and kidney, indicating these as primary sites for NLR‐mediated immune responses in M. armatus . Selection pressure analysis using CodeML identified widespread purifying selection across teleost NLRs, alongside multiple positively selected sites in NLRC5 (7 sites in site model, 5 in branch‐site model) and NLRX1 (2 sites in site model, 22 in branch‐site model). These findings provide fundamental insights into NLR‐mediated immunity in M. armatus and contribute to understanding the evolution and function of NLR genes in teleosts.